2022
DOI: 10.2106/jbjs.21.00892
|View full text |Cite
|
Sign up to set email alerts
|

Osseous Morphological Differences in Knee Osteoarthritis

Abstract: Background: Improved understanding of the morphological characteristics of knees with osteoarthritis (OA) and various deformities can enable personalized implant positioning and balancing in total knee arthroplasty in an effort to continue improving clinical outcomes and optimizing procedural value. Therefore, the purpose of this study was to outline morphological differences in the medial and lateral distal femur and proximal tibia associated with varus and valgus deformities in knee OA.Methods: A large compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…In the present study, unsupervised learning was applied on a large cohort of degenerative knee joints to asses distinct patterns in cartilage wear and establish the relation with limb alignment and local joint geometry. The polynomial autoencoder revealed medial and lateral wear to be related to respectively varus and valgus malalignment, confirming previously published findings (Sharma et al, 2010;Sharma et al, 2013;Dell'Isola and Steultjens, 2018;Siddiqi et al, 2022). However, Siddiqi and colleagues assumed coronal plane malalignment being rather a response than a cause of knee OA.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, unsupervised learning was applied on a large cohort of degenerative knee joints to asses distinct patterns in cartilage wear and establish the relation with limb alignment and local joint geometry. The polynomial autoencoder revealed medial and lateral wear to be related to respectively varus and valgus malalignment, confirming previously published findings (Sharma et al, 2010;Sharma et al, 2013;Dell'Isola and Steultjens, 2018;Siddiqi et al, 2022). However, Siddiqi and colleagues assumed coronal plane malalignment being rather a response than a cause of knee OA.…”
Section: Discussionsupporting
confidence: 82%
“…However, Siddiqi and colleagues assumed coronal plane malalignment being rather a response than a cause of knee OA. In contrast, we found it to be present already in a pre-diseased state (Siddiqi et al, 2022). As such, we consider it to be part of an arthritic phenotype rather than being uniquely a result of knee OA.…”
Section: Discussionmentioning
confidence: 55%
“…The degree of the femoral neck anteversion and the morphological parameters of the proximal femur will affect the morphology of the distal femoral trochlea. However, in presented study, this phenomenon only occurs in females 7,8 . Suardi et al .…”
Section: Introductioncontrasting
confidence: 55%
“…However, in presented study, this phenomenon only occurs in females. 7,8 Suardi et al found that an increased abductor angle and an increased height of hip center were associated with lateral compartment OA. 9 Moon et al focus on the gender difference of the incidence rate of the lateral KOA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, OA of the knee joint is often accompanied by a disorder of the axis of the lower extremity. Specifically, dominant damage to the articular cartilage of the medial compartment of the knee is most often a consequence of varus knee deformity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%